Effects of acute cervical stretching on arterial wall elastic properties - Ikebe, Harumi; Oi, Naoya; Makino, Akitoshi; Kume, Daisuke; Ishido, Minenori; Nakamura, Tomohiro; Nishiwaki, Masato (Frontiers in Physiology, 2023)
Purpose: Acute (immediate) or regular (mid- or long-term) stretching increases arterial compliance and reduces arterial stiffness. Stretching is widely known to induce arterial functional factor changes, but it is unclear whether stretching alters arterial structural factors. Ultrasound shear wave elastography can quantify the distribution of tissue elastic properties as an index of arterial structural factors. This study thus aimed to examine the effects of acute cervical stretching on arterial wall tissue elastic properties. Methods: Seventeen healthy young adults participated in two different trials for 15 min in random order on separate days: a resting and sitting trial (CON) and a supervised cervical stretching trial (CS). In CS, subjects performed 10 different stretches. At each site, the stretch was held for 30 s followed by a 10-s relaxation period. In CON, subjects rested on a chair for 15 min. Results: After the experiment, carotid arterial compliance, assessed by combined ultrasound imaging and applanation tonometry, was significantly increased in CS, but not in CON. However, there was no significant change in tissue elasticity properties of the arterial wall in either trial, as assessed by ultrasound shear wave elastography. Conclusion: Acute cervical stretching significantly increased carotid artery compliance in young participants, but did not reduce elastic tissue properties (i.e., arterial structural factors) of the carotid artery wall. These results strongly suggest that changes in structural factors have little relation to stretching-induced acute increases in arterial compliance.